2020
DOI: 10.31688/abmu.2020.55.1.05
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial investigating the impact of interferential therapy on pain, range of motion and quality of life in patients with chronic non-specific low back pain

Abstract: Un essai contrôlé aléatoire analysant l'impact de la thérapie interférentielle sur la douleur, la régularité du mouvement et la qualité de vie chez les patients atteints d'une douleur lombaire chronique non spécifique Introduction. L'électrothérapie est une méthode non pharmacologique, non invasive et simple de traitement des douleurs dorsales qui est aussi appliquée par thérapie interférentielle (IF). L'objectif de l'étude était d'étudier l'effet de la FI sur la douleur, l'amplitude des mouvements et la quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 30 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…The analyzed trials included a total of 91 participants experiencing shoulder pain or LBP. One trial was of medium methodological quality, 63 whereas the other was of high quality 56 . In this comparison, both trials demonstrated significant results regarding the pain-relieving effect of IFC when compared with placebo (Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…The analyzed trials included a total of 91 participants experiencing shoulder pain or LBP. One trial was of medium methodological quality, 63 whereas the other was of high quality 56 . In this comparison, both trials demonstrated significant results regarding the pain-relieving effect of IFC when compared with placebo (Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…Reference [29] study examined the effect of IFC on pain, movement range and quality of life of patients with nonspecific CLBP. Regarding the study sample, 61 patients (30 male, 31 female) participated, aged between 25 and 60 years, and were randomly divided into two groups.…”
Section: Resultsmentioning
confidence: 99%
“…study done on the effect of the interferential therapy in chronic low back pain patients in which interferential therapy was given for 30 minutes and three days per week for four weeks [14].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is used effectively because its penetration in the skin is deep, with minor discomfort. Some of the studies proved that interferential therapy was effective in decreasing pain, increasing lumbar spine mobility, reducing functional limitations and improving quality of life in chronic low back pain patients [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%